Reproductive organ on-a-chip technologies and assessments of the fetal-maternal interface - Richards, Hannah A.; Eastman, Alison J.; Miller, Dusty R.; Cliffel, David E. (Frontiers in Lab on a Chip Technologies, 2024)
In this review, we discuss recent reproductive organ-on-a-chip (OoC) experiments that encompass multiple target areas of investigation, including model fabrication strategies, transport mechanisms, and immunology. We highlight fetal membrane and placental biology, OoC history and background, and the designs of reproductive OoC platforms. Reproductive OoC designs include fetal membrane models such as the Fetal Membrane-on-a-chip (FMOC) and others, placental models such as the placenta on-a-chip, and full reproductive tract models such as EVATAR. Diverse fabrication strategies and the integration of multiple model materials are explored. OoC samples can be analyzed with many analytical techniques, including mass spectrometry, fluorescence microscopy, ELISAs, impedance spectroscopy, and electrochemical techniques. The future of reproductive OoC models is a promising technology for advancing preterm birth (PTB) research, pharmacology studies, and fertility technologies.